Mid-Term Appraisal of Ninth Five Year Plan (1997-2002) Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1997)
Unlike other States of the Union, Arunachal Pradesh has not evolved out from any princely State or segment of British Dominion, through a process of Constitutional development, the area has been formed into a State on 20th Feb'1987. Thus, the State has not inherited any kind of ground infrastructure be it buildings, roads, settled agriculture or so. In 1947 there were only two primary schools and 3 (three) jeepable roads aggregating to a total length of 168 KMs. The development activity in the State therefore, had to be started from scratch after independence.
Government of Arunachal Pradesh, Department of Planning